659 The japanese version of the workplace perma-profiler: a validation study of the measure for well-being at work. (24th April 2018) - Watanabe, K; Kawakami, N; Shiotani, T; Adachi, H; Matsumoto, K; Imamura, K; Yamagami, F; Matsumoto, K; Fusejima, A; Muraoka, T; Kagami, T; Shimazu, A
Abstract : Introduction: The importance of well-being of workers has recently been recognised, since well-being is protective for mortality, independent of negative factors. Although well-being at work is also discussed intensively, no multi-dimensional measure of well-being at work has been developed in a non-western country, such as Japan. The purpose of this study was to investigate the reliability and validity of the Japanese version of the Workplace PERMA-Profiler, which was developed according to a PERMA model, proposed by Seligman (2011) among Japanese workers. Methods: A baseline Internet-based survey was conducted of 310 Japanese workers and part of the respondents (100) were surveyed again at 1 month later. The Workplace PERMA-Profiler (23 items, 3 items per PERMA domain and 8 additional items) was translated according to the international guideline. Job and life satisfaction, work engagement, psychological distress, work-related psychosocial factors, and work performance were also measured for testing the convergent validity. Cronbach's alphas, Intra-class Correlation Coefficients (ICCs), the Standard Error of Measurement (SEM), and the Smallest Detectable Change (SDC) were calculated, and correlational analyses and confirmatory factor analysis were conducted. Result: A total of 310 (baseline) and 86 (follow-up) workers responded and were included for the analyses. Cronbach's alphas and ICCs for scale scores ranged from 0.75 to 0.96. the SDC of the scale ranged from 1.81 to 2.56. Moreover, the scores of the total and 5 factor scales showed moderate-to-strong correlations with job satisfaction, psychological distress, and work-related factors. A 5-factor theory-based model showed not excellent but marginal acceptable fit ( χ2 (80)=351.30, CFI=0.892, TLI=0.858, RMSEA=0.105, SRMR=0.051). Discussion: The Japanese version of the Workplace PERMA-Profiler showed acceptable levels of reliability and validity. This measure could be useful to assess well-being at work and promote well-being research among Japanese workers. However, concepts and measures for well-being at work should be investigated in further studies.